Analysis of Basic Competencies Achievement of Work and Energy of Students Grade XI of SMAN 11 Pangkep - Yaumil Khairin Septiani, Kaharuddin Arafah*, Salmiah Sari (Physics Education, 2024)
This is a descriptive quantitative research aimed to (1) describe the basic competencies achievement of cognitive aspect on Work and Energy topic; and to (2) describe the supporting factors and obstacles in achieving the basic competencies of Work and Energy topic. The subject of this research were 42 student of Class X in SMAN 11 Pangkep. The research instrument used in this research are multiple choice and essay questions which were arranged based on the achievement indicator of the basic competencies. The research results showed that: (1) The percentage of basic competencies achievement was 38% and considered to be in low category. The highest percentage in multiple choice questions is the remember dimension (71,4%%) while the lowest percentage is the apply dimension (58,9%). The highest percentage in essay questions is the apply dimension (76,1%) while the lowest percentage is the apply dimension (44,9%). (2) One of the supporting factors in achieving the basic competencies is the way teacher kept reminding the basic competencies, indicators, and learning objectives, while one of the obstacles is the difficulty which the students faced in mathematical calculation.